1994
DOI: 10.3354/meps107023
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition, metabolic activity and growih of Antarctic krill Euphausia superba during winter

Abstract: Euphausia superba Dana was collected at stations encompassing 3" of latitude in icecovered waters west of the Antarctic Peninsula in winter of 1992 (July-August), and in the same region the previous summer (December-January). There was no significant change in any biometric index (dry weight vs length, carbon vs dry weight, nitrogen vs dry weight, or body C:N). Rates of ammonium excretion in winter were not significantly different from those previously reported for E. superba in summer. It was clear that E. su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 34 publications
(86 reference statements)
5
60
1
1
Order By: Relevance
“…In contrast to other overwintering studies, Huntley et al (1994) reported high feeding activity of krill on small zooplankton organisms such as Oithona and Oncea and Marschall (1988) on sea ice algae in winter. Actually, the latter study took place at the onset of spring and not as the title states in winter (Hempel 1987).…”
Section: Body Lipid and Protein Utilisationmentioning
confidence: 44%
See 2 more Smart Citations
“…In contrast to other overwintering studies, Huntley et al (1994) reported high feeding activity of krill on small zooplankton organisms such as Oithona and Oncea and Marschall (1988) on sea ice algae in winter. Actually, the latter study took place at the onset of spring and not as the title states in winter (Hempel 1987).…”
Section: Body Lipid and Protein Utilisationmentioning
confidence: 44%
“…The seasonal change in light intensity in the Southern Ocean might also be responsible for seasonal variability in metabolic activity (Kawaguchi et al 1986;Torres et al 1994b). Huntley et al (1994) even showed high metabolic rates and feeding activity on zooplankton of krill during winter and suggested that krill did not adopt speciWc mechanisms for overwintering. Until end of the 1990s, although most studies on krill larvae during winter had mainly focused on their distribution and abundance (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the polar lipid group, the cluster analysis also separated those organs and stages with high PC, low triglycerides and PE content lower than 4.5 % (gonad and digestive gland from mature females and fat body from subadults) from those with lower PC, low triglycerides and PE content higher than 4.4% (abdomen from males, mature and post spawn females, and subadults; stomach from mature females and subadults). The relation between wet weight and body length for the population sampled during FIBEX did not differ significantly from relations reported elsewere (Kato et al 1982, Morris et al 1988, Farber-Lorda 1994, Huntley et al 1994. No significant differences were found between maturity stages, and a mean value of the allometric exponent b of 3.12 was computed, suggesting isometric growth (i.e.…”
Section: St9amentioning
confidence: 74%
“…As ®lter feeders, krill feed mainly on phytoplankton. Primary production in Antarctic waters is, however, characterized by high seasonal and spatial variation (El-Sayed and Taguchi 1981;ElSayed and Weber 1982) and, potentially, E. superba can also change to carnivorous feeding at low phytoplankton densities or during the Antarctic winter (Price et al 1988;Lancraft et al 1991;Huntley et al 1994;Atkinson and SnyÈ der 1997;Pakhomov et al 1997). Krill are able to graze on patchy food sources very e ciently (Hamner et al 1983).…”
Section: Introductionmentioning
confidence: 99%